2021
DOI: 10.33546/bnj.1250
|View full text |Cite
|
Sign up to set email alerts
|

Diploma in Nursing or Bachelor of Science in Nursing: Contradictory issues among nurses in Bangladesh

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Perceptions regarding workload as a stressor can include insufficient staff and/or too many non-nursing tasks as sources of workplace stress (Karadzinska Bislimovska et al, 2014 ). Evidence that non-nursing tasks likely account for some of the participants’ perceptions of workload as a stressor comes from the previously mentioned study that observed about 60% of Bangladeshi RNs time working within government systems was taken up with direct patient care (Joarder et al, 2021 ; Rony, 2021 ). The low nurse-to-patient ratio [2 nurses per 10,000 population] (World Health Organization, 2020 ) in Bangladesh may also have influenced perceptions of workload as a stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions regarding workload as a stressor can include insufficient staff and/or too many non-nursing tasks as sources of workplace stress (Karadzinska Bislimovska et al, 2014 ). Evidence that non-nursing tasks likely account for some of the participants’ perceptions of workload as a stressor comes from the previously mentioned study that observed about 60% of Bangladeshi RNs time working within government systems was taken up with direct patient care (Joarder et al, 2021 ; Rony, 2021 ). The low nurse-to-patient ratio [2 nurses per 10,000 population] (World Health Organization, 2020 ) in Bangladesh may also have influenced perceptions of workload as a stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on hospital records obtained as part of the study, the hospital occupancy rate was 131.4%, and the nurse-patient ratio was 1:10 at the MCHs. Bangladesh has 76 percent of the deficit of nurses (Rony, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 Dissatisfaction with work can have a negative effect on the patient-care provider relationship and affect the quality of treatment. 13,14 A high percentages of nurses in Bangladesh are dissatisfied with their jobs due to low facilities, low wages, and poor working environment. 15…”
Section: Job Dissatisfactionmentioning
confidence: 99%
“…[2] As these diseases were shown to increase in colder environments, weather conditions have been identified as one of the top predictors of COVID-19 and Extreme Acute Respiratory Syndrome (SARS) disease. [3][4] A co-oler environment increases the rate of corona-virus incidence. [5] Cold temperatures can cause symptoms that can irritate the airways and lungs, such as coughing and shortness of breath.…”
Section: Introductionmentioning
confidence: 99%